Pengaruh pendapatan usaha dan beban operasional terhadap laba bersih - Dwi Urip Wardoyo; Raihan Aqil Fauzananda Musrady; Hosana Alicia Febriyanti Siagian (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
Income or income is income that arises from the normal activities of the entity and is known by different names such as sales, fees, interest, dividends, royalties and rent. expenses that have protection, namely other uses of assets or loan guarantees within a certain timeframe to send, produce goods, provide services or the like related to ongoing important industrial operations. The purpose of this study was to determine the effect of operations and operating expenses on net income. The data in this study uses secondary data. The method used is literature review. The resulting revenue can be recognized at the time of production progress, production completion, marketing, or at the time of cash collection. Although both of these criteria must be met, the weight of importance for each condition can be different. At the time of marketing, revenue recognition is perfect for recognizing revenue because the characteristics acquired and realized have been fulfilled.